Persistence of the midline septum of the odontoid process: anatomical and radiological study - Iwanaga, Joe; Samrid, Rarinthorn; Kitagawa, Norio; Ishak, Basem; Uchikado, Hisaaki; Keshavarzi, Sassan; Maulucci, Christopher M.; Dumont, Aaron S.; Tubbs, R. Shane (Surgical and radiologic anatomy. [Englische Ausgabe], 2025)
During our screening of the computed tomography (CT) images of the craniocervical junction, we noticed that the odontoid process occasionally contains a highly ossified region in the midline consistent with a bony septum. Given its potential significance, this study aimed to investigate the highly ossified region in the midline of the odontoid process and to discuss its clinical relevance.
Gesehen am 16.12.2025